Macro and Micro Influences Prudential to Profitability of Islamic Commercial Banks in Indonesia with Company Size as Variables Moderation 2019 – 2023 - Zainal Abidin; Mahesa Dwi Prasetyo Utomo; Nur Aulia Keysha Mayasari; Titis Miranti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effect of Net Performing Financing (NPF), Financing to Deposit Ratio (FDR), Inflation, and BI Rate on Return on Assets (ROA) in Islamic commercial banks in Indonesia, with company size as a moderating variable. The research method used is a descriptive study with a quantitative approach. The research data is panel data covering the period 2019 to 2023, which is obtained from the annual reports of Islamic banks and Bank Indonesia. The data analysis technique involves multiple regression analysis with the Moderated Regression Analysis (MRA) approach to evaluate the moderating role of company size. Testing was carried out using Microsoft Excel 2019 and Eviews 12 programs. The results of the study indicate that NPF and FDR have a significant effect on the ROA of Islamic commercial banks in Indonesia. Conversely, Inflation and BI Rate do not show a significant effect on ROA. In addition, company size is proven to significantly moderate the effect of NPF and FDR on ROA but is not significant in moderating the effect of Inflation and BI Rate on ROA. These findings provide insight into the importance of risk management and liquidity management in increasing the profitability of Islamic commercial banks in Indonesia